Empowering Adolescent Girls Via Breast Health App to Improve Cancer Prevention Knowledge - Mutia Nadra Maulida; Nurna Ningsih; Putri Widita Muharyani; Dhia Diana Fitriani; Gaviota Khalish; Asri Bashir (Universitas Malahayati Lampung, 2026)
ABSTRACT Breast cancer is one of the leading causes of death among women in Indonesia, with low levels of knowledge and limited early detection behaviors among adolescent girls identified as important risk factors that require early intervention. This community service activity aimed to improve the knowledge, awareness, and skills of adolescent girls in Meranjat Village regarding early breast cancer prevention using the Breast Health application as a digital educational medium. The program integrates health education with application-based technology as an innovative strategy to enhance preventive behaviors, particularly in rural or semi-peripheral areas where such approaches are still limited. The implementation included health education sessions on breast cancer, demonstrations of breast self-examination techniques (SADARI), installation and training on the use of the Breast Health application, and ongoing assistance in utilizing its educational and reminder features. Evaluation was conducted using a pre-test and post-test design to measure knowledge improvement, along with monitoring participant engagement with the application. The results showed a significant increase in knowledge about early detection of breast cancer, improved ability to perform SADARI correctly and independently, and a high level of acceptance and satisfaction with the use of the application as a learning tool. In conclusion, this program proved effective in enhancing awareness, knowledge, and early detection practices among adolescent girls, with the Breast Health application offering a practical, accessible, and sustainable technology-based educational approach that can be recommended as an innovative model for community-level breast cancer prevention efforts. Keywords: Adolescent Girls, Breast Cancer, Early Detection, Health Education.